2021
DOI: 10.1186/s12933-021-01434-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of healthy lifestyle including a healthy sleep pattern with incident type 2 diabetes mellitus among individuals with hypertension

Abstract: Background Evidence is limited regarding the association of healthy lifestyle including sleep pattern with the risk of complicated type 2 diabetes mellitus (T2DM) among patients with hypertension. We aimed to investigate the associations of an overall healthy lifestyle including a healthy sleep pattern with subsequent development of T2DM among participants with hypertension compared to normotension, and to estimate how much of that risk could be prevented. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 50 publications
(52 reference statements)
2
23
0
Order By: Relevance
“…Interactions were examined using the interaction term beta in the entire model. The population-attributable risk percent (PAR%) was calculated using the following formula [ 37 ]: where P e is the proportion of the population exposed to the non-low-risk group, and HR is the multivariate-adjusted Cox regression hazard ratio of those participants in the full models.…”
Section: Methodsmentioning
confidence: 99%
“…Interactions were examined using the interaction term beta in the entire model. The population-attributable risk percent (PAR%) was calculated using the following formula [ 37 ]: where P e is the proportion of the population exposed to the non-low-risk group, and HR is the multivariate-adjusted Cox regression hazard ratio of those participants in the full models.…”
Section: Methodsmentioning
confidence: 99%
“…It is inappropriate to directly assume the same implications for the occurrence of CMM in patients already diagnosed with hypertension, as single risk factors play distinct roles at varying stages of the disease [ 13 ]. Recently, a study showed that compared with 0 low-risk lifestyle factors, adhering to 5–6 low-risk lifestyle factors reduced the risk of type 2 diabetes by 86% in patients with hypertension [ 14 ]. These factors included normal body mass index (BMI), non-smoking, moderate alcohol consumption, regular physical activity, healthy diet, and healthy sleep patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Two GWASs of IBS were used, where the discovery set encompassed 53,400 European cases and 433,201 European controls ( Eijsbouts et al, 2021 ) and the validation set was from the FinnGen consortium, including 4,605 cases and 182,423 controls (finn-b-K11_IBS, https://www.finngen.fi/fi ). The IBS cases from UKB should meet at least one of the following four conditions ( Ford et al, 2020 ): digestive health questionnaire (DHQ) Rome III: meet Rome III symptom criteria for IBS diagnosis without other diagnostic explanations for these symptoms ( Vasant et al, 2021 ); DHQ “self-report”: answered “yes” to the question “Have you ever been diagnosed with IBS?‘ ( Stern, 2021 ); Unprompted ‘self-report”: self-reported IBS diagnosis in response to the question “Has a doctor ever told you that you have any serious medical conditions?” ( Song et al, 2021 ); the international code of disease version 10 (ICD-10); with hospital episode statistics indicating being admitted to a hospital due to IBS as the main or secondary ICD-10 diagnosis. The cases from FinnGen all met the ICD-10 standard.…”
Section: Methodsmentioning
confidence: 99%
“…Good quality sleep is essential to maintain physical and mental health ( Stern, 2021 ). Sleep plays an important role in human growth and development, metabolism, and memory function, besides, cardiovascular diseases and metabolic diseases will also be affected by sleep disorders ( Ai and Dai, 2018 ; Ai et al, 2021 ; Song et al, 2021 ). A recent study implicated frequent daytime napping should have deleterious effects on cardiometabolic traits and daytime napping shared genetic loci with both cardiometabolic and neurodegenerative traits ( Dashti et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%